Potential Landuse and Food Production in Watershed Progo - Ritohardoyo, Su (Forum Geografi, 1998)
This paper is an outcome of research concerning spatial differences in forms and coverage of land use in the Progo River Basin. At present the watershed is facing the problem of land use changes from agricultural to non-agriultural ones, leading to the situation of decreasing staple foods. This research is aimed at studying regional variation in the potentials of the research area of the production of staple foods according toland use forms and coverage. Informastion on land use forms and coverage are obtained from the statistical record issued by the Statistical Office of Central Java province and Yogyakarta Speial Provine. As the productivity data on every land use forms are not readily available, the assement on the regional potential is executed on the basis of land use intensity and its apability to produce staple foods. The research reveals that the greatest portion (59 %) of lands in 54 subdistrict in the watershed are highly potential for staple foods production and the rest (41 %) are not potential to moderately potential for staple foods production purpose. The potential for staple foods production in the upper part of the Progo river basin are higher than that in lower part ones. The presence on irrigated land is not always highly potential for staple food production. Although the availability of irrigation water is strongly decisive factor for food prodution (r = 0.661 significant at 99.99 percent), but the presence of built up areas are strongly dictated the potential for food production (r = -0,787 significant at 99.99 percent). The research further shows that the higher the potential for food production, the higher population size (r = 0.791) significant at 99.99 percent). In general it can be concluded that 1) the potentials for food production are determined by the available of irrigation water and the size of the built areas, and 2) the number of population is dictated by the presence of water and potentials for food production.